(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
An attempt was made to evaluate the effect of stocking density on the growth of Heteropneustes fossilis for a period of six months reared in earthen ponds at Rajshahi University Campus. H. fossilis fingerling were stocked at the rate of 320, 280, 240/dec in treatment T1, T2 and T3, respectively, The treatments had significant effects on the weight gain, length gain, ADG, SGR parameters among the treatments. Highest weight gain (45.90g) was observed in T3 and lowest (36.97g) in T1. Significant (P<0.05) highest yield was obtained in case of T2 and T3 and it was 2686.80 kg/ha and 2343 kg/ha, respectively. Higher net benefits (5,18519.91TK/ha) were obtained from treatment T2, than from treatments T1 and T3, water temperature, transparency, pH and dissolved oxygen did not differ significantly (P>0.05) among the treatments depicting the suitable range for fish culture. The plankton levels in all the treatments were found to be at optimum state. Final length, final weight and survival of fingerlings followed the same trends of weight gain. Cost benefit ratio was also highest (1:0.93) in T2, followed by T3 and T1. Overall, highest growth, fish yield survival (95.67%) rate and net benefits of fingerlings were obtained at a density of 280/dec (69, 160 individuals/ha) in treatment T2 were recorded. Bangladesh J. Sci. Ind. Res. 52(4), 253-262, 2017